Characterization of Borrelia burgdorferi strains isolated from Ixodes pacificus ticks in California. - Bissett, M L (1987)
In a survey of 1,714 adult Ixodes pacificus ticks collected in northern California, 24 (1.4%) were found to be infected with spirochetes that reacted with an anti-Borrelia burgdorferi polyvalent conjugate in direct immunofluorescence tests. Eleven isolates of B. burgdorferi from these ticks were characterized by monoclonal antibody, polyacrylamide gel electrophoresis, and Western blot (immunoblot) analyses. Ten of the isolates had molecular and antigenic characteristics similar to those of other U.S. isolates. One strain, cloned by limiting-dilution techniques, was different from any previously reported U.S. strain, but similar to reported European strains. The cloned strain, DN127-Cl9-2, did not react with monoclonal antibodies to Osp A and Osp B major proteins found in most of the U.S. strains. It exhibited an abundant protein with an apparent molecular weight of 25,000.